2011
DOI: 10.1091/mbc.e10-12-1014
|View full text |Cite
|
Sign up to set email alerts
|

The singleDrosophilaZO-1 protein Polychaetoid regulates embryonic morphogenesis in coordination with Canoe/afadin and Enabled

Abstract: Analysis of the function of the fly ZO-1 homologue Polychaetoid shows that it is not essential for junctional assembly or maintenance but does play an important role in embryonic morphogenesis. The data suggest that it works with Canoe/afadin and the actin regulator Enabled to regulate actin anchoring at junctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 69 publications
3
80
0
Order By: Relevance
“…Although Rap1 has been shown to regulate N-cadherin-based AJs and polarity in neuronal cells (Jossin and Cooper, 2011), the upregulation of N-cadherin in the lens epithelium of Rap1 cKO mice could be a secondary response to the altered epithelial plasticity and EMT noted in these lenses since elevated levels of collagen in cells undergoing EMT have been shown to upregulate N-cadherin (Shintani et al, 2008). The loss of ZO-1 based cell adhesive interactions observed in Rap1 deficient lenses in this study support earlier observations reported in cultured epithelial cells and in Drosophila lacking Rap1 and its effector molecule afadin (Choi et al, 2011; Mandai et al, 2013; Mandell et al, 2005; Ooshio et al, 2010; Pannekoek et al, 2009). These changes could be also arising in part from impaired formation of AJs, because conditional deletion of E-cadherin has been shown to impair formation of ZO-1-based cell-cell junctions in the mouse lens epithelium (Pontoriero et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Although Rap1 has been shown to regulate N-cadherin-based AJs and polarity in neuronal cells (Jossin and Cooper, 2011), the upregulation of N-cadherin in the lens epithelium of Rap1 cKO mice could be a secondary response to the altered epithelial plasticity and EMT noted in these lenses since elevated levels of collagen in cells undergoing EMT have been shown to upregulate N-cadherin (Shintani et al, 2008). The loss of ZO-1 based cell adhesive interactions observed in Rap1 deficient lenses in this study support earlier observations reported in cultured epithelial cells and in Drosophila lacking Rap1 and its effector molecule afadin (Choi et al, 2011; Mandai et al, 2013; Mandell et al, 2005; Ooshio et al, 2010; Pannekoek et al, 2009). These changes could be also arising in part from impaired formation of AJs, because conditional deletion of E-cadherin has been shown to impair formation of ZO-1-based cell-cell junctions in the mouse lens epithelium (Pontoriero et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…We propose that cingulin, ZO-1, paracingulin, and PLEKHA7, together with afadin and other regulatory and cytoskeletal proteins, [50][51][52] are part of a molecular framework that links TJ to AJ (Fig. 1), and thus the apical to the lateral domain of polar-ized epithelial cells, by orchestrating the formation of a continuous circumferential belt at the apical junctional complex.…”
Section: Resultsmentioning
confidence: 99%
“…The Drosophila Afadin ortholog, Canoe, is critical for linking the actin cytoskeleton to the AJ during the mechanical stresses of development (Choi et al, 2011; Sawyer et al, 2011). Additionally, Afadin appears to play a role in regulating actomyosin-mediated paracellular permeability through its interactions with the TJ transmembrane protein JAM-A, ZO-2 and PDZ-GEF1; this complex regulates apical actomyosin contraction via the small GTPases Rap2 and RhoA (Monteiro et al, 2013).…”
Section: Scaffold Proteins Regulate Rho Gtpase Output At Cell-cell Jumentioning
confidence: 99%